474 INTRAUTERINE GROWTH RESTRICTION INCREASES INSULIN GROWTH FACTOR 1 PROMOTER MESSENGER RIBONUCLEIC ACID LEVELS IN THE BRAIN. (1st January 2006) - Humphrey, C.; Langen, R.; McKnight, R. A.; Callaway, C. W.; Yu, X.; Lane, R. H.
Abstract : Background: Intrauterine growth restriction (IUGR) leads to neurodevelopmental delay that persists throughout life. Brain growth and development is regulated by cerebral insulin growth factor 1 (IGF-1). Previous work has shown that IGF-1 transcription involves multiple initiation start sites from 2 distinct promoters, with promoter 1 predominating. Alternative splicing within exon 4 accounts for the IGF-1 variants A (IGF-1A) and B (IGF-1B). These characteristics suggest that cerebral IGF-1 transcription may be regulated by epigenetic mechanisms. Objective: We hypothesized that IUGR affects IGF-1 promoter utilization and thereby alters IGF-1 mRNA levels in postnatal brain tissue. Design/Methods: We employed a rat model of IUGR that involves bilateral uterine artery ligation on day 19 of gestation. Rat brain tissue was collected on day 21 from IUGR and sham ( N = 6). mRNA levels of IGF-1A, IGF-1B, promoter 1, and promoter 2 transcription start sites were quantitated with real-time RT- PCR. Results: mRNA data are reported as % of control values. Day 21 IUGR female IGF-1B mRNA levels increase to 201 ± 9.4%*** of control. However, in the day 21 males there was no significant differential expression in IGF-1B. In both the IUGR females and males, IGF-1A was reduced (74.4 ± 12.5%* of control and 60.8 ± 8%** of control, respectively). Interestingly, day 21 IUGR female IGF-1 promoter 1 and promoter 2 were both increased over control (197.3 ± 22.1%* and 191.6 ± 28.6%, * respectively) and were unchanged in the males (* p = < .05, **< .01, ***< .001) Conclusions: IUGR results in postnatal alteration of IGF-1 mRNA in the brain. In IUGR females, regulation of IGF-1 expression leads to increased transcription from promoter 1 and promoter 2. We have previously shown that IUGR leads to persistent changes in epigenetic determinants of chromatin condensation in the female brain. Therefore, we speculate that IUGR alteration of epigenetic determinants leads to increased promoter utilization of IGF-1 in the brain. Supported by the CHRC.